2018
DOI: 10.1038/s41598-018-20358-5
|View full text |Cite
|
Sign up to set email alerts
|

‘Cold shock’ increases the frequency of homology directed repair gene editing in induced pluripotent stem cells

Abstract: Using CRISPR/Cas9 delivered as a RNA modality in conjunction with a lipid specifically formulated for large RNA molecules, we demonstrate that homology directed repair (HDR) rates between 20–40% can be achieved in induced pluripotent stem cells (iPSC). Furthermore, low HDR rates (between 1–20%) can be enhanced two- to ten-fold in both iPSCs and HEK293 cells by ‘cold shocking’ cells at 32 °C for 24–48 hours following transfection. This method can also increases the proportion of loci that have undergone complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 24 publications
5
54
2
Order By: Relevance
“…The The distribution of efficiencies is shown in Figure 1, clearly demonstrating the 3-fold lower efficiency for HDR (median = 0.199) compared to NHEJ (median = 0.606) when choosing targets traditionally. These values are comparable to previous work (21)(22)(23).…”
Section: A Dataset Of Genome-wide Hdr Efficienciessupporting
confidence: 92%
“…The The distribution of efficiencies is shown in Figure 1, clearly demonstrating the 3-fold lower efficiency for HDR (median = 0.199) compared to NHEJ (median = 0.606) when choosing targets traditionally. These values are comparable to previous work (21)(22)(23).…”
Section: A Dataset Of Genome-wide Hdr Efficienciessupporting
confidence: 92%
“…Our results corroborate these findings and reveal that cut-to-insertion-site distance is a critical factor for successful knock-in. Lower knock-in efficiency achieved with the distal-cutting gRNAs could be attributed to ‘partial HDR’ events ( Guo et al, 2018 ), which are not detectable in our ICC end-point assays. Although beyond the scope of our present study, whole-genome sequencing of the CRISPR-edited bulk cells can shed light on the extent of ‘partial HDR’ events in epitope knock-in experiments.…”
Section: Discussionmentioning
confidence: 83%
“…For example, if the eggs are kept at 6 °C, it takes about three months until hatching, in stark contrast to two days for zebrafish. Interestingly, it has been reported that cold shock-treatment increases the frequency of HDR gene editing in induced pluripotent stem cells 51 .…”
Section: Discussionmentioning
confidence: 99%